Analisis Variabel Yang Mempengaruhi Alih Fungsi Lahan Kota Batu - Karerarena (Jurnal Ilmu Ekonomi, 2022)
The purpose of this study is to determine the extent to which the success of economic development in Batu city and the influence of agriculture, production of holticultural, hotel accommodation labor and open of unemployment rate in Batu city. The method used in this study using mutiple regression and classic assump analysis method. The results of this study indicate that the area of agricultural that have been converted to tourism. Especiallyy in hotel accommodation, has no impact on the economy of human resources. This can be caused by the phenomenon of urbanization and th equality of community independence in improving skill is very good. While the results of the mutiple regression research show that partially, Hotel Accommodation have a negative and significant effect on agriculture. Meanwhile, iproduction of holticultural, labor and open of unemployment rate has a negative and insignificant effect on agriculture. Simultaneously, production of holticultural, hotel accommodation, labor and open of unemployment rate have a significant positive effect on agricultural of Batu City in 2003-2020.